The vanished collection - Baer de Perignon, Pauline (New Vessel Press, 2022)
"It all started with a list of paintings. There, scribbled by a cousin she hadn't seen for years, were the names of the masters whose works once belonged to her great-grandfather, Jules Strauss: Renoir, Monet, Degas, Tiepolo and more. The list drove Pauline Baer de Perignon on a frenzied trail of research that takes her from the occupation of France to the present day as she breaks the silence around the wrenching experiences her family never fully transmitted, and asks what art itself is capable of conveying over time" --